Energy Aware Routing Protocols for Wireless Mobile Ad hoc Networks: A Review - Rajeswarappa, G; S, Vasundra (International Journal of Computer Sciences and Engineering, 2019)
A wireless network is a multi-hop connection where each mobile node collaborates to form a network without using any infrastructure such as access points or base stations. It has important properties such as dynamic topology, restricted bandwidth and limited resources, which are major challenge to improve the use of energy resources which are the key aspects during the design of modern ad hoc network architecture. The nodes in the wireless ad hoc network have inadequate range of transport, and their processing and storage capacities in addition to their energy resources are inadequate. This resource constraint in ad hoc wireless networks creates significant challenges in effective routing to achieve better productivity in high-traffic network. This paper presents a review of the various issues and challenges in the power routing and optimization protocols during communication in the wireless network designed to improve the life span of the network for a longer period.